Teacher’s Autonomy Support and Engagement in Math: Multiple Mediating Roles of Self-efficacy, Intrinsic Value, and Boredom - Wang, Jia; Liu, Ru-De; Ding, Yi; Xu, Le; Liu, Ying; Zhen, Rui (Frontiers in Psychology, 2017)
Previous studies have highlighted the impacts of environmental factors (teacher’s autonomy support) and individual factors (self-efficacy, intrinsic value, and boredom) on academic engagement. This study aimed to investigate these variables and examine the relations among them. Three structural equation models tested the multiple mediational roles of self-efficacy, intrinsic value, and boredom in the relation between teacher’s autonomy support and behavioral, emotional, and cognitive engagement, respectively, in math. A total of 637 Chinese middle school students (313 males, 324 females; mean age = 14.82) voluntarily participated in this study. Results revealed that self-efficacy, intrinsic value, and boredom played important and mediating roles between perceived teacher’s autonomy support and student engagement. Specifically, these three individual variables partly mediated the relations between perceived teacher’s autonomy support and behavioral and cognitive engagement, while fully mediating the relation between perceived teacher’s autonomy support and emotional engagement. These findings complement and extend the understanding of factors affecting students’ engagement in math.